Sistem Informasi Pemesanan Baju Olahraga Berbasis Web Pada Konveksi “Adher” Tammerodo Sendana Majene - Maspiati; Nasruddin; Musliadi KH (Scientific Literacy Innovation and Technology Journal, 2024)
The very rapid development of technology is currently bringing us into the era of modernization, almost all aspects of human life are very dependent on technology, this is because technology was created to help and make it easier for humans to complete an activity or job. The impact of technological developments on daily life and aims to optimize sportswear sales services through a web-based application, "Adher". The waterfall method is used for the implementation phase with a focus on friendly user interface design. The app includes features-login, main menu, products, about us, payment confirmation and contact us. Integrated system analysis with data flow diagrams, database relations, and user interface design. It is hoped that this method will provide an effective solution to meet the sales needs of "Adher" convection, increase efficiency, and make it easier for consumers to order sportswear online. Based on the results of the research that has been carried out, it can be concluded that the Web-Based Sportswear Ordering Information System at the "Adher" Convection, Tammerodo Sendana District, Majene Regency includes: Product Data, customer data, payment transaction data, information data, user data whose processing is based on The website database is running according to its function. The implementation of the Sportswear Ordering System can help customers or consumers easily visit convections online without having to go to the convection because they only need to open the link address for ordering sportswear at Adher convection.